Quantitative assessment of household waste composition and segregation pattern in urban settings of Ujjain, Madhya Pradesh: a pick analysis/waste composition analysis study - Kalyanasundaram, Madhanraj; Krishnan, Kavya; Raj, Dharma; Singh, Surya; Parashar, Vivek; Vishwakarma, Deepmala; Soni, Rachna; Sahoo, Krushna Chandra; Sabde, Yogesh; Pathak, Ashish; Purohit, Manju; Atkins, Salla; et al. (Frontiers in Sustainability, 2026)
IntroductionEffective management of municipal solid waste (MSW)is a persistent challenge in India, where rapid urbanization and limited infrastructure contribute to unscientific disposal practices. Household (HH) waste constitutes the largest share of MSW, yet reliable data on its generation and composition remain scarce. This study presents a baseline assessment conducted in Ujjain, Madhya Pradesh, as part of the I-MISS intervention on HH waste segregation.MethodologyA cross-sectional survey was undertaken among 215 HHs across slum and non-slum areas. Waste was collected daily for seven consecutive days, sorted into 23 predefined fractions, and analyzed for per capita and per HH-level generation, composition, and mis-sorting.ResultsFindings reveal an average daily per capita generation of 141.0 g and 146.7 g,and per HH generation of 651.4 g. Organic waste formed the largest fraction (69.1%), followed by plastics, paper, and textiles. Nearly half (48.1%) of the dry waste stream was mis-sorted, mainly due to organic and sanitary fractions being placed incorrectly. Mis-sorting was more pronounced in slum HHs, particularly for sanitary and hazardous sharp waste. Statistical analysis highlighted that family size, house type, and socio-economic status (SES) significantly influenced waste generation patterns, with smaller HHs and middle-income groups producing more waste.DiscussionThe study underscores the urgent need to strengthen HH-level segregation through targeted behavioral interventions and improved infrastructure. Emphasizing composting, recycling, and the safe disposal of sanitary and hazardous waste can enhance resource recovery and reduce environmental risks. These findings provide crucial evidence to inform urban waste management policies and design locally appropriate, sustainable strategies for Indian cities.